2020
DOI: 10.21608/jappmu.2020.78854
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adding Green Synthesized Gold Nanoparticles to Tris-Extender on Sperm Characteristics of Cryopreserved Goat Semen

Abstract: There are various challenges during semen cryopreservation used for artificial insemination, oxidative stress is considered as the major factor. Usage of nano-particle materials is an efficient tool to overcome these challenges. In the present article, effects of adding green synthesized gold nanoparticles (GSGNPs, 5; 10ppm/mL) to Tris-extender on sperm characteristics in post-equilibrated and post-thawed semen. Apoptosis and sperm ultrastructure post-thawed were also examined as well as enzyme activity and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Human sperm treated with zinc oxide (ZnO) microparticles of size 30-50 μ during cryopreservation resulted in an increase in the motility rate with significantly lower T A B L E 1 Different NPs, their mode and purpose of delivery in fish reproduction 54 Gold NPs of size 19.28 nm prepared by green synthesis method and mixed with tris extender improved the post-thaw sperm parameters of buck sperm. 55 In another study, the supplementation of curcumin NPs (average size 100 nm) with the extender during cryopreservation improved the quality of post-thawed rabbit semen. 56 The motility, viability and antioxidant capacity of the sperm were increased while the percentage of necrotic cells was drastically reduced.…”
Section: Cryopreservationmentioning
confidence: 97%
“…Human sperm treated with zinc oxide (ZnO) microparticles of size 30-50 μ during cryopreservation resulted in an increase in the motility rate with significantly lower T A B L E 1 Different NPs, their mode and purpose of delivery in fish reproduction 54 Gold NPs of size 19.28 nm prepared by green synthesis method and mixed with tris extender improved the post-thaw sperm parameters of buck sperm. 55 In another study, the supplementation of curcumin NPs (average size 100 nm) with the extender during cryopreservation improved the quality of post-thawed rabbit semen. 56 The motility, viability and antioxidant capacity of the sperm were increased while the percentage of necrotic cells was drastically reduced.…”
Section: Cryopreservationmentioning
confidence: 97%
“…The addition of green synthesized gold nanoparticles (GSGNPs) (10 ppm) to a Tris-based extender improved buck semen freezing by maintaining the sperm membrane and acrosome integrity post-thawing. In addition, GSGNPs improved antioxidant capacity and consequently scavenged ROS in a buck semen extender [88]. GSGNPs are nontoxic and possess several medical applications [89].…”
Section: Metal Nanoparticles and Sperm Cryopreservationmentioning
confidence: 99%
“…Magnetic-conjugated NPs have been shown to successfully select superior sperm among metal-coated boar semen [ 146 ]. In addition, gold NP may have enhanced acrosomal integrity and reduced oxidative stress by scavenging ROS in the goat [ 64 ]. No toxic effect of NPs on sperm has been reported, but gold NPs have been shown to accumulate in the nucleus of sperm [ 64 ].…”
Section: Biomaterials In Gamete and Embryo Cryopreservationmentioning
confidence: 99%
“…In addition, gold NP may have enhanced acrosomal integrity and reduced oxidative stress by scavenging ROS in the goat [ 64 ]. No toxic effect of NPs on sperm has been reported, but gold NPs have been shown to accumulate in the nucleus of sperm [ 64 ]. Recently, Rubio et al showed that Vitamin E NPs suppressed oxidative stress and preserved mitochondrial activity by reducing ROS and LPO in cryopreserved deer sperm [ 136 ].…”
Section: Biomaterials In Gamete and Embryo Cryopreservationmentioning
confidence: 99%
See 1 more Smart Citation